Polarization but Not Pillarization Catholicism and Cultural Change in Post-Transformation Poland - Sadłoń, Wojciech (Religions, 2021)
The modern Polish cultural system emerges through the interplay between social structure and agency, which represent different properties and powers or, more precisely, ‘independent properties, capable of exerting autonomous influences.’ I argue that Polish Catholicism entered the transformation process to some extent as an agential force which shaped progressive social change and delivered ‘energy’ for the transformation of Polish society. However, the process of transformation has changed the public position of the Catholic Church as it is no longer an actor within a dominating social movement that thrived in the quest for freedom and human rights. Catholicism that has played a role in shaping social conflicts, still represents to some degree ‘a public good’. That is why, despite strong political polarization in Poland, there is no context for ‘pillarization’ within Polish society. The situation of Catholicism in the modern Polish social configuration should be described using the category of ‘polarization’ rather than ‘pillarization’. My study of Polish Catholicism confirms that social polarization in Poland is not a bottom-up process but rather, is driven from the top down as a cultural process.